Implementasi Algoritma Brute Force Pada Sistem Pertanahan di Balai Desa - Ajeng Tri Rahayu; Mukhtar Hanafi; Maimunah Maimunah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Development epoch in era globalization like current information systems utilizing computer technology which is very sophisticated and modern will facilitate data processing which can save time and cost. Result information obtained will facilitate data processing which can save or agencies that utilize artificial intelligence humans or is often called artificial intelligence (AI). Processing data and information fast and efficiently are important things which are needed by an agency, one is office hall village. Processing or archiving books C or Letter C this village still uses manual methods with recording or writing data at books archives villages and views reworked sequence number parcel book C or Letter C previous: to record numbers on owners of old land and owner new land. The way is certainly not efficient because it will require a lot of books and take a lot of time to record data on ownership of land. Objective of this study i.e. implement algorithm brute force to facilitate the search owners land previous on archive electronic. Method development on a system which is used in research is a brute force algorithm in searching for land data, string matching is a part of the string search process. The resulting land data is very dependent on the technique or algorithm carried out in matching the string. In this study, the algorithm used in string matching is brute force. This algorithm performs matching strings with shifts one by one patterns and adjusts them to text so that between Pattern and Text have patterns which are equal. Results analysis of studies This is in the form of trials trial matching strings-with algorithms brute force with studies case using search or search engine with programming language PHP to matching strings.